Analisis Media Pembelajaran Berbasis Deep Learning pada Pembelajaran Biologi Tingkat SMA - Dina Alfiyana; Laili Fatrotul Munawaroh; Mutiara Sabila; Lussana Rosita Dewi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The application of deep learning-based learning media as a pedagogical approach that emphasizes meaningful learning and in-depth conceptual understanding in biology learning at the high school level is still relatively limited. This study aims to analyze the application of deep learning-based learning media in biology learning at the high school level and identify relevant media types to improve student motivation and in-depth conceptual understanding. The method used is a literature review by systematically analyzing 14 relevant scientific articles published between 2021-2025. Articles were obtained through Google Scholar, DOAJ, and ScienceDirect databases. The results of the literature review indicate three main patterns. First, deep learning focuses on meaningful, reflective, and contextual learning. Second, interactive digital media integrated with learning models has proven effective in increasing learning motivation, active engagement, and higher-order thinking skills. Third, the implementation of deep learning-based media still faces obstacles such as limited technological infrastructure, low teacher digital literacy, and resistance to conventional learning. The synthesis of these findings confirms that the effectiveness of deep learning-based media is highly dependent on the alignment between media design and the applied pedagogical strategy. Therefore, a learning media development strategy that integrates deep learning principles is needed. Thus, deep learning-based media has the potential to become a strategic tool in realizing meaningful, contextual, and 21st-century biology learning.